An aerosol particle containing enriched uranium encountered in the remote upper troposphere. (April 2018) - Murphy, D.M.; Froyd, K.D.; Apel, E.; Blake, D.; Blake, N.; Evangeliou, N.; Hornbrook, R.S.; Peischl, J.; Ray, E.; Ryerson, T.B.; Thompson, C.; Stohl, A.
Abstract: We describe a submicron aerosol particle sampled at an altitude of 7 km near the Aleutian Islands that contained a small percentage of enriched uranium oxide. 235 U was 3.1 ± 0.5% of 238 U. During twenty years of aircraft sampling of millions of particles in the global atmosphere, we have rarely encountered a particle with a similarly high content of 238 U and never a particle with enriched 235 U. The bulk of the particle consisted of material consistent with combustion of heavy fuel oil. Analysis of wind trajectories and particle dispersion model results show that the particle could have originated from a variety of areas across Asia. The source of such a particle is unclear, and the particle is described here in case it indicates a novel source where enriched uranium was dispersed. Highlights: We describe a highly unusual aerosol particle containing a very small amount of enriched uranium. The bulk of the particle probably came from combustion of heavy fuel oil. The particle was encountered when we were making no special attempt to sample radioactive material. We don't know the source for this particle. It may indicate a novel source where enriched uranium was dispersed.